The Influence of Creativity, Price Determination to Publicity and Their Impact to the Purchasing Power of Customers - FEBRIANTI, Adjeng Mariana (Journal of Environmental Management and Tourism, 2018)
The business world is demanded to be more creative to face increasingly tight competition. By coming into effect of the ASEAN Economic Community (MEA), many global competitors began to target the Indonesian market. The purpose of this research is to know songket development in Sukadana Village, Jonggot Sub-district, Central Lombok. The research method used descriptive verificative method through hypothesis testing, modelling approach using SEM, with the selected samples as many as 150 customers. The results revealed that the ability to weave is not supported by enough science; this ability is obtained in the hereditary, so that indirectly affects the buying interest. The reduction of prices cannot be sure to improve competitiveness with fellow songket weaver. It can be concluded that indirectly price determination influences the buying interest. Creativity has a correlation with price determination: the higher the creativity is created, the higher the price is offered.